PENGGUNAAN COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI HASIL BELAJAR SISWA SMP - Saraswati, Dandan Luhur; Ishafit, Ishafit (Jurnal Pendidikan Fisika, 2015)
Physics lessons in addition considered a very frightening specter because it filled with formulas, often learning application too monotonous and boring that is by using learning CDs. It is what lies behind this action research. This study aims to decide students motivation and achievement results for physics lesson after using cooperative learning type Numbered Heads Together (NHT).The study was conducted in SMP Muhammadiyah Yogyakarta 9. This type of research is a classroom action research settingVIII A class totaling 40 students. learning model used is a model of cooperative learning type Numbered Heads Together (NHT). Plan 2 cycles of research conducted and completed in the second cycle. Data were collected with a learning achievement test results, observation sheets and questionnaires. The analysis is descriptive qualitative.Results motivation questionnaire given to each learning cycle is obtained in the first cycle is 65% of students in both categories, 35% of students in the classical category of less and 66.3%. In the second cycle of 80% of students in the excellent category, 20% of students in both categories and in the classical as much as 95% of students have had a very good learning motivation. Achievement of learning outcomes of students has increased significantly as the first cycle were 21 students approximately 52.5% declared complete with an average grade of 6.17, while the lowest value 4.5 and the highest value of 7.5, the second cycle of the average value of the class to 8.29 with the percentage of classical completeness 100% with the lowest value of 6.7 and the highest 10.